2008
DOI: 10.1038/sj.bjc.6604695
|View full text |Cite
|
Sign up to set email alerts
|

Tallness is associated with risk of testicular cancer: evidence for the nutrition hypothesis

Abstract: The pathogenesis of testicular germ cell tumours (GCTs) is potentially influenced by high-energy nutrition during infancy. As adult height is a proxy for childhood nutrition, we investigated the role of nutrition in GCT pathogenesis by comparing stature of patients with healthy men. In a matched case -control study, 6415 patients with GCT were compared with healthy army conscripts (1:6 matching modus) with regard to height (cm) and body mass index (BMI; kg/m 2 ). Statistical analysis involved tabulation of des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…For lipid level, we define risk alleles as variants that are positively associated with total cholesterol and LDL, the increased level of which is known to confer risk of heart disease, but negatively associated with HDL, the increased level for which is considered protective. For height, although such definitions are more ambiguous, we considered variants that are positively associated with height as a risk allele because increased mortality has been previously reported for taller subjects (16)(17)(18)(19).…”
Section: −30mentioning
confidence: 99%
“…For lipid level, we define risk alleles as variants that are positively associated with total cholesterol and LDL, the increased level of which is known to confer risk of heart disease, but negatively associated with HDL, the increased level for which is considered protective. For height, although such definitions are more ambiguous, we considered variants that are positively associated with height as a risk allele because increased mortality has been previously reported for taller subjects (16)(17)(18)(19).…”
Section: −30mentioning
confidence: 99%
“…A number of studies have reported that increased adult height may be a risk factor for TC, thereby suggesting that factors related to adult height may also be related to risk of these tumors (Richiardi et al, 2007, Dieckmann et al, 2008, Lerro et al, 2010. Dieckmann et al (2008) found that very tall men (>195 cm) carried a TC risk of OR: 3.35 (95% confidence intervals (CI): 2.88-3.90; adjusted).…”
Section: Heightmentioning
confidence: 99%
“…Dieckmann et al (2008) found that very tall men (>195 cm) carried a TC risk of OR: 3.35 (95% confidence intervals (CI): 2.88-3.90; adjusted). In the STEED Study, there was a statistically significant increased risk of TC associated with greater height, and this association was particularly evident in men with seminomas (Lerro et al, 2010).…”
Section: Heightmentioning
confidence: 99%
“…However, the Hamburg team around Dieckmann [1] reports no such fi ndings, and the hypothesis is further negated by other studies [8,9], whose results are, if anything, contrary.…”
Section: Discussionmentioning
confidence: 89%